The Muskox ( Ovibos moschatus) - Glover, R. (Oryx, 1953)
On 26th June, 1689, an English youth, named Henry Kelsey, and an Indian boy set out northwards on a month-long journey from a newly-founded trading post at the mouth of the Churchill River in Hudson Bay. Their object was to find Indians who might bring furs to the new post, but they hiked an estimated 200 miles out and back over the Barrens without meeting a single human being. If, however, their trip was commercially a fruitless, as well as an arduous enterprise, they still made one discovery of some scientific interest. On Sunday, 9th July, Kelsey recorded in his diary: “in y e Evening spyed two Buffillo left our things & pursued y m Kill'd one they are ill shapen beast their Body being bigger than an ox leg & foot like y e same but not half so long a [long] neck & head a hog their Horns not growing like other Beast but joyn together upon their forehead & so come down y e side of their head & turn up till y e points be Even w th ye Buts their Hair is near a foot long” (Doughty and Martin, 1929, pp. 27–8).